Willingness to pay for vaccines in China: A systematic review and single-arm Bayesian meta-analysis - Yi Li; Ziwei Liu; Liangru Zhou; Ruifeng Li (Human Vaccines & Immunotherapeutics)
The effective implementation of vaccination heavily depends on the society’s willingness to pay (WTP). There is currently a dearth of comprehensive evidence about WTP for vaccines in China. This systematic review aims to review studies on the WTP for vaccines, to summarize factors affect WTP in China. Base-case analysis and Sensitivity analysis of WTP for every vaccine were estimated via single-arm Bayesian meta-analysis. A total of 28 studies were included for systematic review. The point estimates and 95% Credible Interval of pooled WTP for influenza and HPV (9-valent) vaccine were $27.409 (23.230, 31.486), $464.707 (441.355, 489.456). Influencing factors to WTP were age, income, peer influence, health condition and etc. Future research should give focus to improving sample representativeness and survey tool, conducting intervention trials, identifying effective methods to promote WTP.